Syriac in Mesopotamia (Journal of the College of Basic Education, 2023)
Syriac origin in MesopotamiaThe first global civilization is the civilization of Mesopotamia, and no one doubts its antiquity, originality, or advancement. Rather, discoveries and research increase our conviction, day after day, that the impact of the successive civilizations of Mesopotamia through many eras far precedes the eras of prosperity of other world civilizations.